2001
DOI: 10.1124/mol.60.1.26
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, Expression, Signaling Mechanisms, and Membrane Targeting of P2Y11Receptors in Madin Darby Canine Kidney Cells

Abstract: The P2Y(11) receptor is hypothesized to link to both G(s) and G(q), although this proposition is based on expression and separate assays of G(s) and G(q) function in different cell types [J Biol Chem 1997;272:31969-31973]. We have cloned and characterized a canine P2Y(11)-like (cP2Y(11)) receptor from cultured Madin Darby canine kidney (MDCK-D1) cells. When cP2Y(11) receptors are expressed in canine thymocyte (CF2Th) cells that normally lack functional purinergic responses, ADP beta S stimulates phosphatidylin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 19 publications
1
47
1
Order By: Relevance
“…20 and data not shown). These findings suggested that the receptor responsible for the indo-insensitive effect is not the P2Y 1 receptor but instead is another receptor, perhaps the P2Y 11 receptor, which in MDCK-D 1 cells also responds to adenine bisphosphates (14,21).…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…20 and data not shown). These findings suggested that the receptor responsible for the indo-insensitive effect is not the P2Y 1 receptor but instead is another receptor, perhaps the P2Y 11 receptor, which in MDCK-D 1 cells also responds to adenine bisphosphates (14,21).…”
Section: Resultsmentioning
confidence: 90%
“…Cells were used in assays at 60 -80% confluency. GFP-tagged cP2Y 11 receptor-overexpressing MDCK-D 1 cells were cultured from the stable cell line prepared by Zambon et al (14).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lanthanum inhibits UTP-induced Ca 2+ mobilization in MDCK cells [164]. P2Y 1 , P2Y 2 and P2Y 11 receptor mRNA was shown to be expressed by MDCK cells, but the P2Y 2 receptor was dominant in mediating ATP activation of cAMP formation [155,295,373,427]. A later paper showed expression of P2Y 6 (as well as P2Y 1 , P2Y 2 and P2Y 11 ) receptors in MDCK cells [142].…”
Section: Distal Tubulesmentioning
confidence: 99%
“…In mammals, eight P2Y receptors have been cloned and proven to be nucleotide receptors, either activating phospholipase C (P2Y 1 , P2Y 2 , P2Y 4 and P2Y 6 ) or inhibiting adenylyl cyclase (P2Y 12 , P2Y 13 and P2Y 14 ). Uniquely, P2Y 11 activates both phospholipase C and adenylyl cyclase [2,3]. In humans P2Y 11 is selective for ATP [2] but in dogs it is selective for ADP [3].…”
Section: Introductionmentioning
confidence: 99%